Pengembangan E-Modul Interaktif Berbentuk Flipbook Pada Materi Sistem Ekskresi Untuk Kelas XI SMA : (Development of an Interactive E-Module in the Shape of a Flipbook on Excretory System Material for Class XI SMA) - Rahayu, Erni; Sadikin, Ali; Hamidah, Afreni (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
Industrial Revolution 4.0 requires the world of education to adapt to technology. One way to improve the quality of learning is to develop innovative learning media, such as interactive e-modules in the form of flipbooks. This research aims to develop an excretion system material e-module and analyze the suitability of the media, analyze teacher and student perceptions and the validity of the module. This research uses the R&D method using the ADDIE development model which consists of (1) Analyze, (2) Design, (3) Develop, (4) Implementation and (5) Evaluation. The types of data in this research are qualitative and quantitative data. Data collection uses material validation questionnaires, media validation, teachers and students. The tests were analyzed using SPSS 27 software. The test subjects were students and teachers of SMAN 8 Muaro Jambi. The results show that the e-module product in the form of a flipbook on excretory system material can be used in the learning process. The e-module feasibility results were obtained through material and media validation, material validation was carried out three times with a percentage of 90% and media validation was carried out twice with a percentage of 90%, both of which were in the